2011
DOI: 10.1603/ec10446
|View full text |Cite
|
Sign up to set email alerts
|

Use of Systemic Fipronil and Imidacloprid to Control Regeneration Pests of Loblolly Pine

Abstract: Regeneration pests of loblolly pine (Pinus taeda L.) threaten growth and survival in intensively managed loblolly pine plantations throughout the southeastern United States. The Nantucket pine tip moth, Rhyacionia frustrana (Comstock), in particular, often reduces growth of loblolly pine but has been difficult to control with traditional insecticides due to multiple annual generations and multi-year infestations which are difficult to predict in timing and location. Relatively new systemic insecticide products… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…Sublethal effects included a significant reduction in the survival and fecundity as well as increased mortality in the first and subsequent generations. Asaro and Creighton ( 2011 a, b) noted that loblolly pines appeared to be protected from the Nantucket pine tip moth ( Rhyacionia frustrana ) even 1 year after treatment, and the treatment effect apparently was not confined to the target pest species, but extended to further non-target insect species.…”
Section: Terrestrial Invertebratesmentioning
confidence: 99%
“…Sublethal effects included a significant reduction in the survival and fecundity as well as increased mortality in the first and subsequent generations. Asaro and Creighton ( 2011 a, b) noted that loblolly pines appeared to be protected from the Nantucket pine tip moth ( Rhyacionia frustrana ) even 1 year after treatment, and the treatment effect apparently was not confined to the target pest species, but extended to further non-target insect species.…”
Section: Terrestrial Invertebratesmentioning
confidence: 99%
“…Because weed control is a necessary part of plantation silviculture [6,24] but represents a significant expense [12], we wanted to examine relative species performance with and without competition control. Finally, as it has been shown that protection of new pine plantations from common insect pests can greatly enhance establishment success and early productivity [32,33], we wanted to test whether use of a commercially available systemic insecticide had any benefit for establishing hardwood SRWC bioenergy plantations.…”
Section: Introductionmentioning
confidence: 99%
“…Forest products that we use every day, such as paper towels, mulch, diapers, and paper, are all created from the most economically important timber species in the Southeast, loblolly pine ( Pinus taeda L.) (Pinales: Pinaceae) (Schultz 1999). However, intensively managed loblolly pine plantations are vulnerable to a number of pathogens and pests that alter wood quality and production, including the Nantucket pine tip moth (NPTM) ( Rhyaciona frustrana Comstock) (Lepidoptera: Tortricidae), an abundant and ubiquitous pest in young pine plantations (Schultz 1999, Asaro and Creighton 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In the 1960s, the systemic insecticides phorate and disulfoton were assessed (Cade and Heikkenen 1965, Rauschenberger et al 1969). However, new systemic insecticide classes with less mammalian toxicity and extended efficacy for NPTM management set the stage for more recent reevaluations of systemic insecticide use (Asaro and Creighton 2011, King et al 2014). Systemic insecticides for NPTM management can be applied as a soil injection, soil drench, tablet, or injected into containerized seeding plugs where the chemicals are then absorbed and translocated throughout the seedling.…”
Section: Introductionmentioning
confidence: 99%